Strategi Pemasaran Program Green Laboratory Menuju Green Hospital dengan Metode Segmenting, Targeting, and Positioning Serta Marketing Mix di Rsup Dr. Sardjito, Yogyakarta - Purbosari, Purbosari (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2020)
Health services have the main objective of improving health and preventing disease with the community as the main target. The demand for service needs from hospital customers has shifted towards a complete service based on the comfort and safety of the hospital environment. The green hospital policy is the answer to the shift in demands for the quality of hospital services for the community. In an effort to realize Dr. Sardjito as an environmentally friendly hospital (green hospital), the Integrated Laboratory Installation (ILK) has great potential to contribute through its role as a green laboratory. One of the efforts that have been started by ILT Dr. RSUP. Sardjito is through a paperless laboratory policy. The laboratory as one of the elements in a hospital is obliged to place aspects of ecological, social and aesthetic balance as the basis for every policy formulation through optimizing environmental management and empowerment, so that the existence of a laboratory with the complexity of its activities does not add to the negative burden of environmental pollution, and even provides positive benefits. for environmental sustainability of the surrounding community. Hospitals must have good marketing strategy planning, quality and quality, to increase patient interest in using their services. Thus, it is necessary to determine a marketing strategy based on the determination of market segmentation, target market, and market position for the program. The marketing mix or marketing mix is a marketing strategy consisting of product, price, place, promotion, and often develops into 7Ps with the addition of people, process and physical evidence. Marketing mix strategies influence each other. Green Laboratory as one of the leading concepts that can be marketed to improve service quality and consumer interest.